Time-Resolved Measurement of Interatomic Coulombic Decay in Ne2 - Schnorr, K.; Senftleben, A.; Kurka, M.; Rudenko, A.; Foucar, L.; Schmid, G.; Broska, A.; Pfeifer, T.; Meyer, K.; Anielski, D.; Boll, R.; Rolles, D.; et al. (My University, 2013)
The lifetime of interatomic Coulombic decay (ICD) [L. S. Cederbaum et al., Phys. Rev. Lett. 79, 4778 (1997)] in Ne2 is determined via an extreme ultraviolet pump-probe experiment at the Free-Electron Laser in Hamburg. The pump pulse creates a 2s inner-shell vacancy in one of the two Ne atoms, whereupon the ionized dimer undergoes ICD resulting in a repulsive Ne+(2p−1)−Ne+(2p−1) state, which is probed with a second pulse, removing a further electron. The yield of coincident Ne+−Ne2+ pairs is recorded as a function of the pump-probe delay, allowing us to deduce the ICD lifetime of the Ne+2(2s−1) state to be (150±50) fs, in agreement with quantum calculations.